ALMUSTRA: An Augmented reality application for introducing traditional musical instruments - Mailoa, Evangs; Widyasari, Elvira Resti (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2024)
Traditional Indonesian musical instruments reflect the richness and diversity of culture and are an integral part of people's lives. However, in recent decades, it has faced challenges in preserving and introducing it to the younger generation. Arts and Culture teachers in Junior High School at Salatiga face difficulties in showing examples of the shapes and sounds of traditional musical instruments from various regions in Indonesia. Augmented reality (AR) technology is emerging as an innovative tool to introduce and preserve local knowledge about traditional musical instruments. This research uses a mixed-method approach which combines qualitative and quantitative data collection. Data collection was carried out through semi-structured interviews with junior high school arts and culture teachers. For system development, the Multimedia Development Life Cycle (MDLC) method is used with the aim of producing multimedia learning products. This research resulted in an Android application called ALMUSTRA: Introduction to Traditional Musical Instruments Based on Augmented Reality. ALMUSTRA is a learning product that helps introduce Indonesian traditional musical instruments, equipped with 3D images, sounds, and quizzes as gamification to make the teaching and learning process more interesting.